Translocation experiment gives new insights into the navigation capacity of an African duck. (7th March 2022) - Cumming, Graeme S.; Henry, Dominic A. W.; Reynolds, Chevonne
Abstract: Aim: Movement is integral to the distribution and abundance of wildlife. We undertook an experimental test of the navigation capacity of Egyptian Geese Alopochen aegyptiacus to better understand the movements of moult‐migratory waterfowl and the implications of navigation capacity for their ecology. Location: Southern Africa. In June 2015, we translocated six post‐flightless moult Egyptian Geese 1250 km south, from north‐west South Africa (Barberspan) to the south‐west coast (Strandfontein). We compared their movements to those of 29 previously tracked resident Egyptian Geese from the source and translocation sites, and three additional sites (Voelvlei; Jozini Dam; Lake Manyame, north‐central Zimbabwe). Methods: We used solar‐powered satellite GPS to track movement patterns and compared the movement paths of different birds using net‐squared displacement analysis and multiple regression analysis of different measures of movement paths. Results: Over time periods up to 658 days, none of the translocated Egyptian Geese returned to Barberspan and only one appeared to fly towards it. Translocated birds showed some novel and risky behaviours. Longer, searching‐type movements were evident with the onset of both the breeding and moulting seasons. Quantitative comparisons suggested that translocated birds retained elements of learned behaviours. Main conclusions: Navigation by Egyptian Geese appears to have a strong learned (internal) element, with long‐distance movement triggered by internal states such as the need to moult. Translocated animals modified their movement patterns in ways that mostly allowed them to survive. Our results have interesting implications for understanding the dynamics of individual populations; a strong reliance on learned behaviours may explain the unresolved conundrum of why no African duck species has colonized Europe without human assistance. Our analysis demonstrates the complexity of influences on animal movement and highlights the importance of navigation capacity for conservation biogeography.